Association between intravenous fluid resuscitation and outcome among patients with suspected infection and sepsis: A retrospective cohort study. (12th November 2021) - Kabil, Gladis; Liang, Sophie; Delaney, Anthony; Macdonald, Stephen; Thompson, Kelly; Saavedra, Aldo; Suster, Carl; Moscova, Michelle; McNally, Stephen; Frost, Steven; Hatcher, Deborah; Shetty, Amith
Abstract: Objective: To investigate the association between timing and volume of intravenous fluids administered to ED patients with suspected infection and all‐cause in‐hospital mortality. Methods: Retrospective cohort study of ED presentations at four metropolitan hospitals in Sydney, Australia, between October 2018 and May 2019. Patients over 16 years of age with suspected infection who received intravenous fluids within 24 h of presentation were included. Results: During the study period, 7533 patients with suspected infection received intravenous fluids. Of these, 1996 (26.5%) and 231 (3.1%) had suspected sepsis and septic shock, respectively. Each 1000 mL increase in intravenous fluids administered was associated with a reduction in risk of in‐hospital mortality (adjusted odds ratio [AOR] 0.87, 95% confidence interval [CI] 0.76–0.99). This association was stronger in patients with septic shock (AOR 0.66, 95% CI 0.49–0.89), and those admitted to intensive care unit (ICU) (AOR 0.74, 95% CI 0.56–0.96). Patients with suspected sepsis and septic shock who received a total volume of >3600 mL had lower in‐hospital mortality (AOR 0.44, 95% CI 0.22–0.91; AOR 0.16, 95% CI 0.05–0.57) compared to those administered <3600 mL within the first 24 h of presenting to the ED. There was no association between the time of initiation of fluids and in‐hospital mortality among survivors and non‐survivors (2.3 vs 2.5 h, P = 0.50). Conclusion: We observed a reduction in risk of in‐hospital mortality for each 1000 mL increase in intravenous fluids administered in patients with septic shock or admitted to ICU suggesting illness severity to be a likely effect modifier. Abstract : Early recognition and management of sepsis remains challenging for emergency physicians because of current clinical uncertainty particularly regarding fluid resuscitation. Our retrospective cohort study shows that patients who received larger volumes of fluids showed a decrease in all‐cause in‐hospital mortality risk with every 1000 mL increase. This association was stronger in patients with septic shock and those admitted to intensive care unit suggesting that severity of illness is a likely effect modifier.